Impacts of oil price, exchange rate and inflation on the economic activity of Malaysia - Mantai, Mohammed Mahmoud; Alom, Fardous (Wiley Blackwell, 2016)
The purpose of this study is to examine the short and long-run impacts of crude oil price (CP), exchange rate (EXR) and inﬂation (CPI) on the economic activity (GDP) of Malaysia within the framework of the vector error correction model (VECM). The results suggest that CP positively affects GDP in the short-run and the tests do not identify any signiﬁcant impacts of EXR and CPI on the GDP. However, all these variables maintain a long-run relationship with GDP. The causality tests have shown unidirectional Granger causality that run from CP to GDP and not from EXR and CPI to GDP. The ﬁndings of this study are expected to provide insights for practitioners and policy makers to understand the impacts of the CP shocks and its spillovers in the economic activity of Malaysia.